The Thyroid Condition and Residual Clinical Signs in 31 Existing Endemic Neurological Cretins After 42 Years of Iodine Supplementation in China - Li, Jianshuang; He, Yanhong; Ren, Bingxuan; Zhang, Zhaojun; Meng, Fangang; Zhang, Xiaoye; Zhou, Zheng; Li, Baoxiang; Li, Fan; Liu, Lixiang; Shen, Hongmei (Frontiers in Endocrinology, 2022)
Abstract Backgroud: Endemic cretinism is the most severe manifestation among the iodine deficiency-related disorders. The clinical status of the cretins may be modified subsequently by the duration and severity of the disease. We aimed to reassess the clinical status and thyroid function of 31 surviving "neurological cretins" after 42 years of iodine supplementation in a historically severely iodine deficiency area of China. Methods: It was a cross-sectional study in design and we investigated all 31 surviving neurological cretins and 85 controls. A detailed neurological examination was conducted on each patients. All the participants were given a questionnaire and underwent B-mode ultrasonography of the thyroid. The serum levels of thyroid hormones, thyroid antibodies, serum iodine concentration (SIC) and urine iodine concentration (UIC) were measured. Results: The neurological cretins had shorter stature than that of the control. Neurological damage is still present in patients with cretinism. The prevalence of subclinical hypothyroidism and thyroid nodule in the cretins was significantly higher (χ2=4.766, P=0.029 and χ2=17.077, P<0.0001, respectively) compared with the control. After adjusting for confounding factors, endemic neurocretinism was found to be an independent risk factor for subclinical hypothyroidism (OR=4.412; 95% CI: 1.358–14.334; P=0.014) and thyroid nodule (OR=6.433; 95% CI: 2.323–17.816; P<0.0001). Conclusions: Iodine supplementation after birth does not reverse the neurological damage that results from maternal/foetal hypothyroidism in utero and is subsequently manifested as neurological cretinism. There is a cross-sectional association between endemic neurocretinism and subclinical hypothyroidism and thyroid nodule.